Tessituras da impostura : as confissões de Felix Krull em constelação estética negativa - Pandolfo, Alexandre Costi (2016)
This is an essay of aesthetic expression written for doctoral thesis purposes, and it explores the work Confessions of Felix Krull, from Thomas Mann. In order to understand this particular work from Thomas Mann, the author also permeates other works by the german writer. The analysis has its central philosophical basis on the Aesthetic theory of Theodor Adorno. The main concepts worked in this writing are mimesis, subjectivity and the idea of natural history. Another concepts such as essay, constellation, montage and model are also mobilized to understand the object of the thesis. The objective is to comprehend a particular structure of the hegemonic language in the western world, taking into consideration this singular work from Thomas Mann, which he had started writing in 1910 and finally published in 1954. The work was divided into three axes of analysis: one on the expression and language of the Confessions, the other on the narrator subject and on the impostor who confesses, and, finally, the analysis of a scene where the author sought uniqueness as critical and dialectical expression.